Anticoagulant Management and Outcomes in Nontraumatic Intracranial Hemorrhage Complicated by Venous Thromboembolism: A Retrospective Chart Review - Gorman, Johnathon; Candeloro, Matteo; Schulman, Sam (Thrombosis and Haemostasis, 2023)
Background There are limited data on anticoagulant management of acute venous thromboembolism (VTE) after spontaneous intracranial hemorrhage (ICH).Methods We reviewed retrospectively all cases diagnosed with VTE during hospitalization for spontaneous ICH at our center during 15 years. Anticoagulation management outcomes were (1) timing after ICH of anticoagulant initiation for VTE treatment, (2) use of immediate therapeutic dosing or stepwise dose escalation, and (3) the proportion achieving therapeutic dose. Primary clinical effectiveness outcome was recurrent VTE. Primary safety outcome was expanding ICH.Results We analyzed 103 cases with VTE after 11 days (median; interquartile range [IQR]: 7–22) from the diagnosis of ICH. Forty patients (39%) achieved therapeutic anticoagulation 21.5 days (median; IQR: 14–34 days) from the ICH. Of those, 14 (35%; 14% of total) received immediately therapeutic dose and 26 (65%; 25% of total) had stepwise escalation. Anticoagulation was more aggressive in patients with VTE >14 days after admission versus those with earlier VTE diagnosis. Twenty-two patients (21%) experienced recurrent/progressive VTE—less frequently among patients with treatment escalation within 7 days or with no escalation than with escalation >7 days from the VTE. There were 19 deaths 6 days (median; IQR: 3.5–15) after the index VTE, with significantly higher in-hospital mortality rate among patients without escalation in anticoagulation.Conclusion Prompt therapeutic anticoagulation for acute VTE seems safe when occurring more than 14 days after spontaneous ICH. For VTE occurring earlier, it might also be safe with therapeutic anticoagulation, but stepwise dose escalation to therapeutic within a 7-day period might be preferable.
Keywords: anticoagulants; intracranial hemorrhage; venous thromboembolism; hospitalization; outcomes